An experimental investigation of a PCM-based heat sink enhanced with a topology-optimized tree-like structure - Ho, Jin Yao (2022)
A heat sink filled with phase change material (PCM) is an efficient thermal management device which utilizes the high latent heat of fusion of PCM in the cooling process. To improve the thermal performance of the PCM-based heat sink, a topology optimization (TO) strategy is devised to develop a new class of enhanced structures. This is achieved by carrying out a comprehensive numerical study to identify the effects of various thermal transport mechanisms on the TO design by considering two different heat transfer problems, i.e., steady-state heat conduction and transient heat conduction with phase change. To enable easy fabrication and performance evaluation of the new heat sink design predicted by the TO process, the resulting heat sink with tree-like structure was fabricated by selective laser melting (SLM), a metal additive manufacturing (AM) technique. Experimental characterization of the TO heat sink was carried out using three different types of PCMs, i.e., RT35, RT35HC and RT44HC and heat fluxes ranging from 4.00 kW/m2 to 7.24 kW/m2. Our experimental results show that the TO tree-like structure heat sink has better performance, exhibiting up to 4 °C lower wall temperatures, than the conventional fin-structure heat sink. At low heat fluxes, the best thermal performance can be obtained with RT35HC whereas at high heat fluxes, lower wall temperatures were achieved with RT44HC. In addition, the tree-like structure increases operational time by up to 13% as compared to the fin-structure heat sink. The better thermal performance of the tree-like structure heat sink is due to its optimized heat conduction paths that allow heat from the concentrated heat source to be efficiently dissipated to the PCM. This work not only demonstrates the potential of enhancing electronics cooling with TO PCM-based heat sinks, but it also outlines key guidelines for the design and implementation of TO structures for other cooling applications.